2012
DOI: 10.3382/ps.2011-01906
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Newcastle disease and other infectious diseases in backyard chickens at markets in Eastern Shewa zone, Ethiopia

Abstract: This study was conducted to estimate the seroprevalence of Newcastle disease (ND), Pasteurella multocida (PM) infection, Mycoplasma gallisepticum (MG) infection, and infectious bursal disease (IBD) and to assess the level of concurrent seropositivity during the dry and wet seasons of the year 2010. In total, 234 and 216 sera were collected during the dry and wet seasons, respectively, from unvaccinated backyard chickens at 4 live poultry markets in 2 woredas (districts) of Eastern Shewa zone, Ethiopia, and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
48
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 36 publications
13
48
8
Order By: Relevance
“…However, the finding was lower than previous report in Debre Berhan (28.7%) and Sebeta/ Nazaret areas (38.33%) [14]. ND prevalence of 6% and 5.9% in the wet and dry seasons respectively findings had reported from Eastern Shewa zone [6]. On the other hand, higher report (43.68%) was also recorded in central Ethiopia among local scavenging chickens kept under traditional management system [4].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…However, the finding was lower than previous report in Debre Berhan (28.7%) and Sebeta/ Nazaret areas (38.33%) [14]. ND prevalence of 6% and 5.9% in the wet and dry seasons respectively findings had reported from Eastern Shewa zone [6]. On the other hand, higher report (43.68%) was also recorded in central Ethiopia among local scavenging chickens kept under traditional management system [4].…”
Section: Discussioncontrasting
confidence: 54%
“…The highest prevalence in this finding was obtained from Adama Districts (16.7%) followed by Bishoftu (10%). The result has found in accordance with the previous report in Eastern Shewa who reported a prevalence of 24.2% and 14.2% in dry and wet seasons, respectively [6]. However, the finding was lower than previous report in Debre Berhan (28.7%) and Sebeta/ Nazaret areas (38.33%) [14].…”
Section: Discussioncontrasting
confidence: 35%
See 1 more Smart Citation
“…However, published information, either serological or virological, on ND epidemiology in Ethiopia is limited. A few cross-sectional studies in backyard chickens have showed that the disease is present with reported individual seroprevalences ranging from 5.6% to 38% (Zeleke et al, 2005;Tadesse, et al, 2005;Getachew, 2009;Chaka, et al, 2012). Epidemiological and molecular investigation to understand the NDV status of backyard chickens has never been done in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Chicken sera used in this study were collected during structured, multistage household and markets cross-sectional surveys of village chickens in Eastern Shewa zone, Ethiopia between September 2009 and September 2010 (Chaka et al, 2012;Chaka et al, 2013). Villages and households within villages as well as markets were selected randomly.…”
Section: Serum Samples and Serological Testingmentioning
confidence: 99%